For a massless Dirac particle by integrating fermion degree of freedom in path integral, effective action is resulted for gauge field

$$l(\psi,\bar\psi,A)=\bar\psi( \gamma^\mu (i \partial_\mu +A_\mu ) ) \psi $$

$$Z= \int D\psi D\bar\psi D A_\mu e^{(i \int d^3x l)}$$

$$S_{eff} =\int D\psi D\bar\psi e^{(i \int d^3x l)}$$

$$S_{eff} =-i ln (det ( \gamma^\mu (i \partial_\mu +A_\mu )))$$

I want to know:

How can I calculate the following equation?

$$S_{eff} =C_1 C_2 $$


$$C_1=- \frac{1}{12} \epsilon^{\mu\nu\rho} \int \frac{d^3p}{(2\pi)^3} tr[ [G(p)\partial_\mu G^{-1}(p)] [G(p)\partial_\nu G^{-1}(p)] [G(p)\partial_\rho G^{-1}(p)] ] $$


$$C_2= \int d^3x \epsilon^{\mu\nu\rho}A_\mu \partial_\nu A_\rho $$

$G(p)$ is fermion propagator and $G^{-1}(p)$ is its inverse.

  • $\begingroup$ First, use the identity $log(det(...))=Tr(log(...))$ (easy to prove with a diagonal matrix). Then expand the log in power of $A$ (and note that $Tr(log(i\gamma^\mu \partial_\mu))$ gives an (infinite) constant that you can forget about). $\endgroup$
    – Adam
    Oct 5, 2013 at 15:24
  • $\begingroup$ I integrate the fermions degree of freedom and find ln det=tr ln. I expxand ln in power of guage potential. I only find green function for Dirac particle. I can not find vertex or partial derivative of inverse green function for Dirac particle. $\endgroup$
    – Sobouti
    Oct 12, 2013 at 8:18

1 Answer 1


$S_{eff} = -i\ln\det(\gamma^\mu(i\partial_\mu+A_\mu)) = -i\text{ tr}\ln(\gamma^\mu(i\partial_\mu+A_\mu)) = -i\text{ tr}\ln(i\gamma^\mu \partial_\mu(1+(i\gamma^\mu \partial_\mu)^{-1}\gamma^\mu A_\mu)) = -i\text{ tr}\ln(i\gamma^\mu \partial_\mu) -i\text{ tr}\ln(1+(i\gamma^\mu \partial_\mu)^{-1}\gamma^\mu A_\mu))$

The first term is $-i\ln\det(i\gamma^\mu (-i)p_\mu) = -i\ln\det(\not p)$ is infinite and so is ignored.

The second term can be expanded: $$\ln(1+(i\gamma^\mu \partial_\mu)^{-1}\gamma^\mu A_\mu))=\sum_{k=1}^\infty\dfrac{(-1)^k}k((i\gamma^\mu \partial_\mu)^{-1}\gamma^\mu A_\mu)^k=\sum_{k=1}^\infty\dfrac{(-i)^k}k\not\partial^{-k} \not A^k = \sum_{k=1}^\infty\dfrac{(-i)^k}kG^{k} \not A^k$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.